ARAHAN ISLAM TENTANG ARAH KIBLAT - Kaddase, Thayyib (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2015)
The issue of qibla direction is a part of Islamic law (fiqh), while Islamic law is a partof Islamic precept itself. The criteria of someoneâs faith and Islamic state which declared bysyahadatain pledge are believing the thruth and performing the order of Allah swt. and ProphetMuhammad saw. included the leadership of Moslem community which implemented by the shiftof qiblat from Baitul Makdis ke Kaâbah) to Masjid al-Haram Mecca. It is an Islamic preceptwhich its truth cannot be refused based on the understanding resulted from rational thingking ofijtihadi that always refers to Islamic rules and values. Moslem community commonly agreesthat the perform of worship especially salat has some requisites for its validity, one of them islook towards qibla. This paper discusses Islamic guide on qibla direction